2022
DOI: 10.1021/acs.langmuir.2c00092
|View full text |Cite
|
Sign up to set email alerts
|

Depth-Dependent Segmental Melting of the Sphingomyelin Alkyl Chain in Lipid Bilayers

Abstract: The chain melting of lipid bilayers has often been investigated in detail using calorimetric methods, such as differential scanning calorimetry (DSC), and the resultant main transition temperature is regarded as one of the most important parameters in model membrane experiments. However, it is not always clear whether the hydrocarbon chains of lipids are gradually melting along the depth of the lipid bilayer or whether they all melt concurrently in a very narrow temperature range, as implied by DSC. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 61 publications
4
12
0
Order By: Relevance
“…In our previous study, we examined the segment‐specific melting of the SSM acyl chain by examining thermal changes in the chemical shifts of deuterated methanol, [ 35 ] which showed similar results to the present results (see Figure 5). However, there is a small difference of about 1°C in the segmental melting point of the C16′ position from the present study.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…In our previous study, we examined the segment‐specific melting of the SSM acyl chain by examining thermal changes in the chemical shifts of deuterated methanol, [ 35 ] which showed similar results to the present results (see Figure 5). However, there is a small difference of about 1°C in the segmental melting point of the C16′ position from the present study.…”
Section: Resultssupporting
confidence: 80%
“…We recently reported the membrane depth dependence of acyl chain melting in lipid bilayers using site‐selective labeled lipids and solid‐state NMR spectra. [ 35 ] We found that sphingomyelin gradually melts from the terminus of the alkyl chains in the bilayers, and the segment near the amide group then melts at a temperature that is higher by about 1.2°C than that determined by differential scanning calorimetry. However, because the level of inaccuracy in temperature measurements was generally large in NMR measurements, we needed to verify these results with higher accuracy using the 2 H chemical‐shift thermometer, ErDOTA‐ d 8 .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations